2015
DOI: 10.5414/cp202388
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of favipiravir, a novel antiviral agent, on QT interval in healthy Japanese adults

Abstract: It is possible to use a smaller number of subjects in thorough QT studies in Japan than in Europe and the US utilizing moxifloxacin as a positive control. There were no detectable effects of favipiravir on the QT/QTc interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 0 publications
0
41
0
4
Order By: Relevance
“…Significant QTc interval prolongation was not identified on ECG images, obtained three and six hours after the favipiravir was administered. [ 12 ] This study did not provide sufficient information about the effects of the treatment dose on the QTc interval and changes in the QTc interval in subsequent days since the loading dose was lower than that used for COVID-19 patients, and the ECG findings were obtained after three and six hours. In the current study, a significant change in the QTc(Bazett) and QTc(Fre) interval was not observed on the ECG images taken 48 h (median) after favipiravir treatment in Group 3 (respectively p = 0.247, p = 0,075).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant QTc interval prolongation was not identified on ECG images, obtained three and six hours after the favipiravir was administered. [ 12 ] This study did not provide sufficient information about the effects of the treatment dose on the QTc interval and changes in the QTc interval in subsequent days since the loading dose was lower than that used for COVID-19 patients, and the ECG findings were obtained after three and six hours. In the current study, a significant change in the QTc(Bazett) and QTc(Fre) interval was not observed on the ECG images taken 48 h (median) after favipiravir treatment in Group 3 (respectively p = 0.247, p = 0,075).…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Favipiravir was not shown to have a detectable effect on QT intervals in a study performed by Kumagai et al on healthy adults that used moxifloxacin as a positive control to enable high-powered statistical analysis. [ 12 ] To the best of our knowledge, the effect of favipiravir on the QTc interval in COVID-19 patients has not been evaluated in any study to date. Thus, the current study objective was to investigate any change in the QTc interval in patients hospitalized due to COVID-19 receiving favipiravir therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite limited experience with favipiravir, we judged it to be the most appropriate agent in this scenario, given the lower risk for QT prolongation, no need for renal-dose adjustments, and no reported drug–drug interactions. Favipiravir was reported as not having caused QT prolongation after single oral doses of 1200 mg and 2400 mg [ 16 ]. However, in one case report in the treatment of Ebola virus, favipiravir prolonged the QT at higher doses [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It subsequently proved activity against several classes of viruses, including EBOV [ 8 ], and was used in both therapy and postexposure prophylaxis during the recent EBOV epidemic in West Africa [ 9 ]. In their recent work, Kumagai and colleagues [ 5 ] found no effect of favipiravir on the QT interval in healthy Japanese adults after administration of single oral doses of favipiravir 1,200 and 2,400 mg. To the best of our knowledge, there are no other studies assessing this issue [ 4 , 10 ]. Our patient was treated with favipiravir doses much higher than those reported by Kumagai and colleagues, i.e., 6 g on day 1 and 2.4 g on the following days, and this could explain a previously unreported effect on QTc interval prolongation.…”
Section: Case Discussionmentioning
confidence: 99%
“…Favipiravir has also been used in the recent epidemic of Ebolavirus (EBOV) in West Africa [ 4 ]. To date, no significant effects of favipiravir on the QT/QTc interval have been detected [ 5 ]. We report a case of QTc interval prolongation during favipiravir therapy in an EBOV-infected patient treated at our institution.…”
Section: Introductionmentioning
confidence: 99%